Moringa oleifera leaf extract suppresses TIMM23 and NDUFS3 expression and alleviates oxidative stress induced by Aβ1-42 in neuronal cells via activation of Akt - Tatcha Balit; Charoensri Thonabulsombat; Permphan Dharmasaroja (Wolters Kluwer Medknow Publications, 2024)
Background and purpose: Oxidative stress plays an important role in Alzheimer's disease (AD) pathogenesis. Moringa oleifera leaf (MOL) extract has been shown to have antioxidant activities. Here, we studied the antioxidative and anti-apoptotic effects of water-soluble MOL extract in an amyloid beta (Aβ)-induced oxidative stress model of AD. Experimental approach: The effect of amyloid beta (Aβ)1-42 and MOL extract on differentiated SH-SY5Y cell viability was assessed by MTT assay. Cells were treated with Aβ-42, MOL extract, or MOL extract followed by Aβ-42. The mitochondrial membrane potential (ΔΨm) and the reactive oxygen species (ROS) were evaluated by flow cytometry and dihydroethidium (DHE) assay, respectively. Western blotting was used to assess the expression of mitochondrial proteins TIMM23 and NDUFS3, apoptosis-related proteins Bax, Bcl-2, and cleaved caspase-3 along with fluorescence analysis of caspase-3/7, and Akt phosphorylation. Findings/Results: MOL extract pretreatment at 25, 50, and 100 μg/mL prevented ΔΨm reduction. At 100-μg/mL, MOL extract decreased TIMM23 and NDUFS3 proteins and DHE signals in Api-42-treated cells. MOL extract pretreatment (25, 50, and 100 μg/mL) also alleviated the apoptosis indicators, including Bax, caspase-3/7 intensity, and cleaved caspase-3, and increased Bcl-2 levels in Aβ-42-treated cells, consistent with a reduction in the number of apoptotic cells. The protective effects of MOL extract were possibly mediated through Akt activation, evidenced by increased Akt phosphorylation. Conclusion and implications: The neuroprotective effect of MOL extract could be mediated via the activation of Akt, leading to the suppression of oxidative stress and apoptosis in an Aβ-42 model of AD.